AI AND EDUCATION: EMPOWERING LEARNERS WHILE SUSTAINING HUMAN-CENTERED VALUES - R.Arslonova (TADQIQOTLAR, 2025)
Abstract: This article explores the intricate relationship between artificial intelligence (AI) and education. It examines AI’s potential to personalize learning, enhance inclusivity, and improve educational quality, while also addressing ethical and social challenges associated with technology integration. The analysis considers pathways for advancing education while preserving human dignity, drawing on UNESCO’s ethical guidelines for AI and the United Nations Sustainable Development Goals (SDGs). Recommendations are proposed for the effective and ethical adoption of AI in education to empower learners and promote equitable access to knowledge.